Nursing care of gastrointestinal dysfunction caused by abnormal changes of cerebral and intestinal axis in a case of intracranial infection treated by auricular acupoint combined therapy (耳穴综合疗法治疗1例颅内感染脑肠轴异常变化所致胃肠功能障碍患者的护理体会) - ZHAO Jianwen (赵建文); FENG Wenying (冯文英); HUANG Yanping (黄砚萍); ZHAO Jing (赵静) (Association of Integrative Nursing, 2024)
To investigate the effect of auricular acupoint combined therapy on gastrointestinal dysfunction caused by abnormal changes of cerebral intestinal axis in 1 case of intracranial infection. The application of auricular point comprehensive therapy (auricular point massage, auricular Bian-stone scraping, auricular acupoint sticking) technology, with emotional nursing, rehabilitation guidance, health education and so on. The gastrointestinal dysfunction of patients was significantly improved. Auricular acupoint combined therapy has a good effect on gastrointestinal dysfunction caused by abnormal changes of cerebral intestinal axis in intracranial infection. (本文总结1例耳穴综合疗法治疗颅内感染脑肠轴异常变化所致胃肠功能障碍的护理经验。基于护理评估和中医辨证, 采用耳穴按摩、耳部砭石刮痧、耳穴贴压综合疗法, 并配合情志护理、康复指导、健康教育护理措施, 有效改善了患者胃肠道功能障碍症状, 对促进患者康复起到积极的作用。)